Communism, Cold War and Commodity Chains: Southeast Asian Labor History in a Comparative and Transnational Perspective. (2020) - Bosma, Ulbe
Abstract : The geographical term "Southeast Asia" dates from the 1930s, and came to denote a topic for academic studies in the early days of the Cold War. As such, it includes Vietnam, Cambodia, Laos, Indochina, Thailand, Myanmar, Malaysia, Brunei, and the Philippines. Southeast Asia has become thoroughly incorporated in the global economy over the past 150 years; first, as a producer of commodities, and later, as a supplier of cheap garments and electronic components. Under Dutch colonialism and British hegemony—the latter established by the conquest of Burma and the imposition of free trade on Siam and the Philippines in the 1850s—Southeast Asia was turned into a key provider of commodities for the industrializing countries. During high colonialism, from 1870 to 1930, the region became increasingly intertwined, via Singapore as the central port and through the role of mainland Southeast Asia as the rice basket for the plantations of maritime Southeast Asia. After the Second World War, the region was the world's most violent frontier of containment for communist expansion. In recent decades, Southeast Asia has become integrated in global commodity chains as a producer of cheap industrial goods, often as a subcontractor for more advanced economies, such as those of Hong Kong, Korea, Taiwan, and later on, Southeast China.